Gambaran kematian neonatal di RSUD Dr. M. Haulussy Ambon. - Magdalena Paunno (MOLUCCAS HEALTH JOURNAL, 2019)
ABSTRACTMost child deaths in Indonesia today occur in the newborn period (neonatal), the first month of life. The probability of a child dying at different ages is 19 per thousand during neonatal mass, 15 per thousand from ages 2 to 11 months and 10 per thousand from ages 1 to 5 years. Delivery assistance by midwives is one of the strategies in reducing maternal and child health problems. In Indonesia the use of delivery assistance by midwives is still low compared to established indicators. One of the efforts to reduce maternal, infant and under-five mortality rates is the provision of Basic Emergency Neonatal Obstetric Services (PONED) facilities in care centers and Comprehensive Emergency Neonatal Obstetric Services (PONEK) in hospitals. This type of research uses descriptive research. The study was conducted on November 4 - December 15, 2019 at Dr. M. Haulussy Ambon. A sample of 51 infants using total sampling techniques. The results of the study found that deliveries performed by health workers more than 50% were performed by mothers, neonatal deaths with a referral system were smaller compared to non-referral neonatal deaths and the age of mothers giving birth 90% were at productive age.Keywords: Neonatal DeathABSTRAK Sebagian besar kematian anak di Indonesia saat ini terjadi pada masa baru lahir (neonatal), bulan pertama kehidupan. Kemungkinan anak meninggal pada usia yang berbeda adalah 19 per seribu selama massa neonatal, 15 per seribu dari usia 2 hingga 11 bulan dan 10 per seribu dari usia 1 hingga 5 tahun. Pertolongan persalinan oleh bidan merupakan salah satu strategi dalam mengurangi masalah kesehatan ibu dan anak. Di Indonesia pemanfaatan pertolongan persalinan oleh bidan masih rendah dibandingkan dengan indikator yang telah ditetapkan.  Salah satu upaya untuk menurunkan angka kematian ibu, bayi dan balita adalah penyediaan fasilitas Pelayanan Obstetri Neonatal Emergensi Dasar (PONED) di puskesmas perawatan dan Pelayanan Obstetri Neonatal Emergensi Komprehensif (PONEK) di rumah sakit. Jenis penelitian mengunakan penelitian deskriptif. Penelitian dilakukan pada tanggal 04 November – 15 Desember 2019 di RSU Dr. M. Haulussy Ambon. Sampel sebanyak 51 bayi dengan menggunakan teknik total sampling. Hasil penelitian ditemukan persalinan yang dilakukan oleh tenaga kesehatan lebih dari 50% dilakukan oleh ibu, kematian neonatal dengan sistem rujukan lebih kecil presentasinya dibandingkan dengan kematian neonatal yang bukan rujukan serta umur ibu yang melahirkan 90% berada pada usia produktif. Kata Kunci : Kematian Neonatal